Recent Advances on the Role of ATGL in Cancer - Zhang, Renshuai; Meng, Jingsen; Yang, Shanbo; Liu, Wenjing; Shi, Lingyu; Zeng, Jun; Chang, Jing; Liang, Bing; Liu, Ning; Xing, Dongming (Frontiers in Oncology, 2022)
The hypoxic state of the tumor microenvironment leads to reprogramming lipid metabolism in tumor cells. ATGL, as an essential lipid metabolism-regulating enzyme in cells, is regulated accordingly under hypoxia induction. However, studies revealed that ATGL exhibits both tumor-promoting and tumor-suppressing effects, which depend on the cancer cell type and the site of tumorigenesis. For example, in breast cancer, elevated ATGL expression is accompanied by enhanced fatty acid oxidation (FAO), enhancing cancer cells' metastatic ability. In prostate cancer, on the other hand, tumor activity tends to be negatively correlated with ATGL expression. This review outlined the regulation of ATGL-mediated lipid metabolism pathways in tumor cells, emphasizing the HIF-1/HIG-2/ATGL axis, PPAR-γ/G0S2/ATGL axis, and FSP-27/EGR-1/ATGL axis. In the light of recent research on different cancer types, the role of ATGL on tumorigenesis, tumor proliferation, and tumor metastasis was systemically reviewed.